Enhancing security risk assessment towards smart maritime industry: a comprehensive analysis of candidate approaches - Ahmed Mohy Ibrahim; Mohamed Abdelfattah; Mohamed Mohasseb; Said Abdelkader (Maritime Research and Technology)
Maritime security risk assessment forms the cornerstone of effective security measures for ships, ports, and port facilities. However, the current security risk assessment approaches lack adequate preparedness to align with the rapid technological advancements and transformations in the smart maritime industry. The main factor groups and parameters for those approaches have to be adapted, in order for the approaches to keep pace with the dynamic developments of potential technological threats.   This paper aims to examine points of strength and weakness in security risk approaches in the maritime industry, with a focus on the transition to a smart maritime industry. It scrutinizes recommended security risk assessment approaches outlined in security guidelines and published research, emphasizing challenges in their selection, by using a descriptive-analytical approach. It also explores their effect on the smart maritime industry when applied to ships such as maritime teleoperated vessels (MTVs), elucidating key concepts. A comparative analysis of selected approaches underscores structural characteristics and values. Finally, the study critically assesses transforming the maritime industry for improved security risk assessment practices for MTVs and their maritime teleoperation centers (MTCs). Findings highlight the necessity for a more comprehensive maritime security risk assessment approach.   Received: 14 February 2024 Accepted: 27 April 2024 Published: 05 May 2024